Efficacy of different mouthwashes against COVID-19: A systematic review and network meta-analysis - Luca Sbricoli; Lucia Schiavon; Giulia Brunello; Paola Brun; Kathrin Becker; Stefano Sivolella (Elsevier, 2023)
To evaluate the effectiveness of antiseptic mouthwashes in reducing SARS-CoV-2 load clinically and in vitro. A systematic electronic search (MEDLINE/Scopus/Cochrane) was conducted to identify prospective clinical and in vitro studies published between 2019 included and 16 June 2023 assessing the effectiveness of mouthwashes in reducing SARS-CoV-2 load in saliva or surrogates. Data were summarized in tables and a network meta-analysis was performed for clinical trials. Thirty-five studies (14 RCTs, 21 in vitro) fulfilled the inclusion criteria. The risk of bias was judged to be high for 2 clinical and 7 in vitro studies. The most commonly test product was chlorhexidine alone or in combination with other active ingredients, followed by povidone-iodine, hydrogen peroxide and cetylpyridinium chloride. Overall, the descriptive analysis revealed the effectiveness of the mouthwashes in decreasing the salivary viral load both clinically and in vitro. Network meta-analysis demonstrated a high degree of heterogeneity. Among these studies, only chlorhexidine 0.20% was associated to a significant Ct increase in the saliva 5 min after rinsing compared to non-active control (p = 0.027). Data from clinical and in vitro studies suggested the antiviral efficacy of commonly used mouthwashes. Large well-balanced trials are needed to identify the best rinsing protocols.